PENGARUH KEPEMIMPINAN TERHADAP PERILAKU KERJA INOVATIF DENGAN BERBAGI PENGETAHUAN SEBAGAI VARIABEL MEDIASI (Studi pada Karyawan PT X) - Nisrina, Salma; Raharja, Edy (Diponegoro Journal of Management, 2024)
ABSTRACT Human resources apply elements that provide support and carry out every stage in organizational functions, including in innovation efforts. Organizations need high quality human resources in order to achieve the goals that have been set. In order for innovative work behavior to be more optimal, organizations can use strong transformational leadership styles and encouragement to share knowledge. This research aims to analyze the influence of transformational leadership on innovative work behaviors by sharing knowledge as a mediation variable in one of the manufacturing companies called PT X. This study uses primary data distributed through online questionnaires on employees at PT X who are research samples, and secondary data from journals, books, and relevant data from companies. This questionnaire was developed by researchers using 5 likert scales. The number of samples used in this study was 95 respondents with the purposive sampling technique. Data analysis techniques use the SmartPLS 3.0 application to test hypotheses and influences between those variables. The results in this study show that transformational leadership has a positive influence and significant on innovative work behavior, transformational leadership has a positive influence and significant on knowledge sharing, and knowledge sharing also shows that there is a positive influence and significant on innovative work behavior. This research also shows that there is an influence of knowledge sharing as a mediation variable between transformational leadership and innovative work behavior.